Prototype River Water Level Detection Tool Using Ultrasonic Sensor with Sound Output Based on Arduino Uno Microcontroller - Chandra, Yudi Irawan; Irawati, Diyah Rury; Riastuti, Marti; Rokoyah, Kokoy (IJISTECH (International Journal of Information System and Technology), 2023)
River water that overflows or is at an uncontrolled height can cause flooding and environmental damage. Therefore, the development of a river water level detector that can provide early warning is very important. In this research, we propose a river water level detector using ultrasonic sensor with sound output based on Arduino Uno microcontroller. This device is designed to measure the level of river water by utilizing the principle of ultrasonic wave reflection. The ultrasonic sensor is installed above the river and sends ultrasonic waves to the water surface. The waves are then reflected back to the sensor after reaching the water surface. The travel time of the reflected wave is used to calculate the distance between the sensor and the river water surface.The Arduino Uno microcontroller is used to process the distance data obtained from the ultrasonic sensor. When the water level exceeds the specified limit, the microcontroller will generate a sound output as a warning. A speaker is connected to the microcontroller and will emit different sounds depending on the water level.This tool has advantages in terms of accuracy and responsiveness. By using ultrasonic sensors, measurements can be taken in real-time and provide water level information with high precision. The voice output also allows the information to be delivered directly and effectively to the user. The test results show that this river water level detection device can work well and provide early warning when the water level exceeds the specified limit. The success of this tool is expected to help in flood risk management and environmental conservation.